Women's Power, Conditional Cash Transfers, and Schooling in Nicaragua - Gitter, Seth R.; Barham, Bradford L. (World Bank, 2012)
The Social Safety Net (Red de Protección Social, RPS) program in Nicaragua is one of many conditional cash transfer programs that pay households cash stipends in exchange for school attendance and regular visits to health clinics by the children. A key feature is that payments go to the female head of household. Previous research suggests that exogenous transfers to women are more likely to be spent on their children's health, nutrition, and education and thus to reinforce the goals of these programs. Randomized experimental data from RPS are used to test for heterogeneous program impacts on school enrollment and spending based on a woman's power, as proxied by her years of schooling relative to her husband's years of schooling. The results confirm previous findings that more household resources are devoted to children when women are more powerful. However, when a woman's power greatly exceeds her husband's, additional female power reduces school enrollment. RPS impacts on schooling are much larger than the expected income effects estimated from the control group, although no evidence is found that female power alters the impact of RPS on school enrollment. The conditionality of RPS is probably decisive. While RPS significantly increases food and education expenditures, the impact is attributable primarily to income effects.